2017
DOI: 10.1111/nmo.13102
|View full text |Cite
|
Sign up to set email alerts
|

Myenteric neuroprotective role of aspirin in acute and chronic experimental infections with Trypanosoma cruzi

Abstract: Early and delayed treatment with low-dose ASA can reduce the morphofunctional damage of colonic myenteric neurons caused by murine T. cruzi infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 55 publications
(170 reference statements)
0
21
0
Order By: Relevance
“…Oliveira et al (2010) observed higher IFN-γ and IL-2 concentrations in serum of rats infected with T. cruzi and treated with meloxicam. Also, increased nitrite production and high numbers of inflammatory infiltrates was observed in the colon of mice infected with T. cruzi and treated with COX-2 inhibitor, regardless of time of infection, or acute or chronic phase (Oda et al, 2017). Additionally, upregulation of IL-1β, nitrite, IL-12, and IL-10 was verified in murine peritoneal macrophages (Malvezi et al, 2014) and human monocytes (Carvalho de Freitas et al, 2017) infected with T. cruzi and treated with aspirin-COX inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Oliveira et al (2010) observed higher IFN-γ and IL-2 concentrations in serum of rats infected with T. cruzi and treated with meloxicam. Also, increased nitrite production and high numbers of inflammatory infiltrates was observed in the colon of mice infected with T. cruzi and treated with COX-2 inhibitor, regardless of time of infection, or acute or chronic phase (Oda et al, 2017). Additionally, upregulation of IL-1β, nitrite, IL-12, and IL-10 was verified in murine peritoneal macrophages (Malvezi et al, 2014) and human monocytes (Carvalho de Freitas et al, 2017) infected with T. cruzi and treated with aspirin-COX inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulated phosphoproteins involved in neurological and inflammatory pathways can damage colonic myenteric neurons during T . cruzi infection [ 20 ]. Bioinformatics analysis of array data also showed an overall increase in the proinflammatory response in HCoEpiC during T .…”
Section: Discussionmentioning
confidence: 99%
“…For this, 10 microscopic fields (20× magnification lens) were analyzed in each section (total area 63.8 cm 2 ). Result was obtained by summing the number of inflammatory cell in all histological sections from the same rat which was projected to 1 cm 2,33 …”
Section: Methodsmentioning
confidence: 99%